Efectos de los porcentajes de jirón y mucílago de chía en una bebida funcional - Pachard Vélez, Erik Abrahan (2024)
The objective of this research was to determine the effect of chia husk and mucilage percentages on the development of a functional beverage, evaluating its antioxidant capacity and its influence on physicochemical, microbiological, and sensory properties. Five treatments with three replicates each were carried out for the beverage, which was prepared with two main components: percentages of chia husk and mucilage. A completely randomized design (CRD) was used, resulting in 15 experimental units of 1000 mL. Physicochemical parameters studied included pH, °Brix, acidity, and total solids, while microbiological parameters included coliforms, fecal coliforms, mesophilic aerobes, molds, and yeasts, as well as total antioxidant activity (ABTS). ANOVA assumptions were applied to the different variables. The obtained physicochemical results were: pH 5.917, °Brix 16.633%, acidity 0.20333%, and total solids 18.090% (see Table 4.2), which were selected as the most optimal results in accordance with regulations, despite not fully meeting the requirements of NTE INEN 2337. Antioxidant capacity showed the best result in T1 with a value of 4.6331 µmol Trolox Equivalent/mL of beverage. The count of mesophilic aerobes exceeded the permissible limits (<10 CFU/mL) according to NTE INEN 2337. Sensory analysis was not performed by untrained tasters; however, compliance was achieved in coliforms, fecal coliforms, molds, and yeasts.